Description of two new species of Cerambycidae and new records and notes on American Cerambycidae and Disteniidae (Coleoptera) - Bezark, Larry G.; Santos-Silva, Antonio (Zootaxa, 2023)
Two new species are described: Dihammaphora erecta sp. nov. (Cerambycinae, Rhopalophorini), from Ecuador; and Colombicallia contraria sp. nov. (Lamiinae, Calliini), from Mexico (Veracruz). Dihammaphora erecta sp. nov. is included in a previous key. Twelve new records from Mexico, Central America, and South America are provided. Variations of the elytral pubescent patterns in Aegomorphus consentaneus and A. polystictus (Bates, 1885) are reported. The unknown female of Aegomorphus cunninghami is examined and illustrated for the first time, and notes on the differences with males are provided. Variation in the pubescent pattern in Aegomorphus quadrigibbus (Say, 1831) is reported.